Fragmentation in accounting : an analysis of international accounting as a catalyst for integration : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Accountancy at Massey University - Locke, Joanne; Locke, Joanne (Massey University, 1996)
The isolation and disconnectedness of areas of research are termed fragmentation. The nature of fragmentation and its impact on accounting is explored in this thesis as it potentially relates to ongoing concerns expressed about accounting research. The concept of fragmentation is considered in the context of a model of knowledge accumulation using a sociological perspective. This sociological approach is found to be a common, unifying theme of writers who take opposing views about methodological issues and the disciplinary status of accounting. It thus provides a basis for a descriptive approach that incorporates the broad spectrum of research styles in accounting. Fragmentation is identified as being embedded and perpetuated in the institutional constructs of academic departments in universities. It is characterised by two features. First, non-homogeneity in the research literature so that research areas cluster into many unrelated groups. Second, a lack of cohesion, that is, a heavy reliance on reference disciplines for theories and methods. The outcomes of fragmentation for a discipline are: a reduction in the efficiency of research as researchers re-discover knowledge already obtained elsewhere in the discipline; a tendency for research in a fragmented area to become inwardly focussed, producing research that lacks relevance outside the group of researchers involved; and the possible ultimate disintegration of the discipline. Mechanisms capable of reducing the impact of fragmentation on a discipline are considered, based on the experience of other disciplines and on current recommendations in accounting. A potential mechanism that operates in harmony with the institutional structures of knowledge production in accounting and that is currently well-placed to stimulate the re-integration of accounting research is identified in the international accounting specialty. Closer investigation of this possibility is undertaken using a co-citation analysis of seventeen years of source articles from the International Journal of Accounting: Education and Research. The co-citation study indicates that the international accounting research literature is fragmented in terms of non-homogeneity, but shows high levels of cohesion. These factors, plus the methodologically eclectic style and broad topic coverage of the specialty, lead to the view that it is a suitable candidate to promote re-integration in accounting. Researchers pursuing topics in the area may achieve an integrating role by simply applying an international perspective to issues in accounting and maintaining the characteristics mentioned. However, to enhance the contribution of the area to integration, specific research strategies are identified. Three research areas provide bridging points to promote integration. They are, a contextual approach to capital markets research, accounting theory, and measurement issues. It is suggested that research in these areas published in widely read journals has the potential to stimulate reintegration in the accounting literature in a way that is compatible with institutional structures.
Keywords: Accounting research